Pengembangan Literasi Digital Untuk Meningkatkan Pembelajaran Melalui Supervisi dan Belajar Kolaboratif pada Guru SDN 1 Jambesari - Romlah, Romlah; Hadi, Syamsul; Sobri, Ahmad Yusuf (Cetta: Jurnal Ilmu Pendidikan, 2025)
Digital literacy ownership affects the role of teachers as learning facilitators when innovating to implement technology, namely creatively selecting and designing digital teaching resources. The effectiveness of these digital teaching resources is because they are easily accessible and have complete references. These characteristics are in accordance with students so that they can increase motivation and learning outcomes. The reflection carried out by the researcher still shows the low digital literacy possessed by educators under his supervision, thus encouraging the researcher to take the initiative to implement supervision and collaborative learning. This step is a form of the researcher's responsibility as the principal to improve the professionalism of his educators so that they are able to achieve organizational goals. This study aims to analyze and study in more depth so that empirical evidence is obtained of the development of teacher digital literacy through supervision and collaborative learning. The focus of this study is to develop the ability to create digital teaching resources, especially learning videos. Action research with the Kemmis TcGart model is carried out through 4 stages in each cycle, namely planning, action, observation and reflection. The next cycle will be carried out to obtain the expected results. This research was conducted at the researcher's school, precisely at SD Negeri 1 Jambesari with 8 teachers as research subjects. Data were collected through observation, interviews and assessment rubrics using observation instruments with a scale of 1-4. In the initial observation, the researcher obtained data on the ability to create digital teaching resources of 76.57 and after taking action in cycle I, the results of the achievement of creating digital teaching resources were obtained with a value of 91.12, then in cycle II a value of 95.46 was obtained. So these results prove that the implementation of supervision and collaborative learning has proven to be able to develop the digital literacy of SDN 1 Jambesari teachers, especially in creating learning videos.